Nucleostemin maintains self-renewal of embryonic stem cells and promotes reprogramming of somatic cells to pluripotency - Qu, Jian (The Rockefeller University Press, 2012)
Nucleostemin (NS) is a nucleolar GTP-binding protein that was first identified in neural stem cells, the functions of which remain poorly understood. Here, we report that NS is required for mouse embryogenesis to reach blastulation, maintenance of embryonic stem cell (ESC) self-renewal, and mammary epithelial cell (MEC) reprogramming to induced pluripotent stem (iPS) cells. Ectopic NS also cooperates with OCT4 and SOX2 to reprogram MECs and mouse embryonic fibroblasts to iPS cells. NS promotes ESC self-renewal by sustaining rapid transit through the G1 phase of the cell cycle. Depletion of NS in ESCs retards transit through G1 and induces gene expression changes and morphological differentiation through a mechanism that involves the MEK/ERK protein kinases and that is active only during a protracted G1. Suppression of cell cycle inhibitors mitigates these effects. Our results implicate NS in the maintenance of ESC self-renewal, demonstrate the importance of rapid transit through G1 for this process, and expand the known classes of reprogramming factors.